2010
DOI: 10.1111/j.1399-5618.2010.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of comorbid obsessive‐compulsive disorder and bipolar disorder in children and adolescents

Abstract: Joshi G, Wozniak J, Petty C, Vivas F, Yorks D, Biederman J, Geller D. Clinical characteristics of comorbid obsessive‐compulsive disorder and bipolar disorder in children and adolescents.
Bipolar Disord 2010: 12: 185–195.
© 2010 The Authors. Journal compilation © 2010 John Wiley & Sons A/S. Objective:  To explore bidirectional comorbidity between bipolar disorder (BPD) and obsessive‐compulsive disorder (OCD) in youth and to examine the symptom profile and clinical correlates of both disorders in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 43 publications
6
52
1
Order By: Relevance
“…As showed in Table 5, studies conducted in adult and child patients reported that the presence of comorbidity between BD and OCD was associated with poorer functioning and poorer quality of life in all the domains (physical, psychological, social, environmental) vs. patients with 'pure' BD or 'pure' OCD (16,31,39,43,51,62,73). Two hospital-based studies presented similar trends without, although not showing statistically significant differences (65,76).…”
Section: Included Studiessupporting
confidence: 54%
See 4 more Smart Citations
“…As showed in Table 5, studies conducted in adult and child patients reported that the presence of comorbidity between BD and OCD was associated with poorer functioning and poorer quality of life in all the domains (physical, psychological, social, environmental) vs. patients with 'pure' BD or 'pure' OCD (16,31,39,43,51,62,73). Two hospital-based studies presented similar trends without, although not showing statistically significant differences (65,76).…”
Section: Included Studiessupporting
confidence: 54%
“…Conversely, three studies showed lower rates of control (53), washing (64,68), ordering, and repeating (64) compulsions in subjects with comorbidity. In the presence of BD, children and adolescents with OCD more frequently were associated with hoarding obsessions and compulsions (43,61,62,72) and ordering (73) compulsions.…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations